1997
DOI: 10.1021/es970347a
|View full text |Cite
|
Sign up to set email alerts
|

Priming Microbial meta-Dechlorination of Polychlorinated Biphenyls That Have Persisted in Housatonic River Sediments for Decades

Abstract: We recently demonstrated a strategy for stimulating or "priming" the indigenous microorganisms to dechlorinate weathered PCBs in sediments, but the dechlorination exhibited a very narrow para-dechlorination specificity. We tested the priming activity of various PCB congeners to discover those that would prime broader and more extensive PCB dechlorination activity. 2,3,4,5,6-Pentachlorobiphenyl (23456-CB), 2346-CB, and 236-CB primed extensive and sustained meta-dechlorination (Process N) of the Aroclor 1260 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 22 publications
2
75
1
3
Order By: Relevance
“…We previously determined that it is necessary to stimulate PCB dechlorination in the sediments studied by the addition of a high concentration (350 M) of a single PCB congener or brominated biphenyl, a procedure that we called priming (6,11,13,64). Hence, we established active PCB-dechlorinating cultures in sediment slurries carrying out Process N dechlorination by priming with 26-BB as previously reported (11).…”
Section: Resultsmentioning
confidence: 96%
“…We previously determined that it is necessary to stimulate PCB dechlorination in the sediments studied by the addition of a high concentration (350 M) of a single PCB congener or brominated biphenyl, a procedure that we called priming (6,11,13,64). Hence, we established active PCB-dechlorinating cultures in sediment slurries carrying out Process N dechlorination by priming with 26-BB as previously reported (11).…”
Section: Resultsmentioning
confidence: 96%
“…The key reductive dechlorination products for process N are PCBs 47, 51,100, while the key dechlorination products in Anacostia sediment were tetra-CBs including PCBs 47, 49 and 53 and tri-CBs including PCBs 28 or 29 and 25 (varying according to the specific replicate). Furthermore, the fact that addition of PCB 116 as an alternate halogenated electron acceptor was not effective in stimulating the dehalogenating population in Anacostia sediment to dechlorinate weathered PCBs, but did stimulated extensive process N dechlorination of the Aroclor 1260 residue in Housatonic River sediment (Van Dort et al, 1997), provide another line of evidence that the observed dechlorination in Anacostia sediment is different from the previously described process N.…”
Section: Pcb Congener Profiles In Anacostia Sediment Microcosms the mentioning
confidence: 83%
“…(Bedard et al, 2006;Fagervold et al, 2007;Van Dort et al, 1997). For example, in earlier studies flanked meta chlorines were preferentially removed, e.g.…”
Section: Pcb Congener Profiles In Anacostia Sediment Microcosms the mentioning
confidence: 99%
See 2 more Smart Citations